Pengaruh Kepemimpinan Transformasional Terhadap Kinerja Personel Melalui Semangat Kerja Sebagai Variabel Intervening: Studi Pada Kepolisian Resort Sampang - R. Aditya Dwi Rubiantoro; Chamariyah Chamariyah; Woro Utari (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
R. Aditya Dwi Rubiantoro, 2025. The Influence of Leadership Style To Performance Work Employees of the Sharia People's Financing Bank (BPRS) Bhakti Sumekar Sumenep Which Is Mediated By Productivity Work . Graduate program University Wijaya Putra Surabaya. Based on his approach study This including in type study explanatory research . Sample study as many as 76 respondents . Objective study This is : 1) For know And analyze whether style leadership own influence in a way direct to performance work of employees of the Sharia People's Financing Bank (BPRS) Bhakti Sumekar Sumenep? 2) For know And analyze whether style leadership own influence in a way direct to productivity work of employees of the Sharia People's Financing Bank (BPRS) Bhakti Sumekar Sumenep? 3) For know And analyze whether productivity Work own influence in a way direct to performance work of employees of the Sharia People's Financing Bank (BPRS) Bhakti Sumekar Sumenep?4) For know And analyze whether style leadership own influence in a way No direct to performance mediated work by productivity Work employees of the Sharia People's Financing Bank (BPRS) Bhakti Sumekar Sumenep?Results study show that: 1) style leadership influential significant to performance work of employees of the Sharia People's Financing Bank (BPRS) Bhakti Sumekar Sumenep with mark original sample of 0.257. 2) style leadership influential significant to productivity work of employees of the Sharia People's Financing Bank (BPRS) Bhakti Sumekar Sumenep with mark original sample of 0.542. 3) productivity Work influential significant to performance work of employees of the Sharia People's Financing Bank (BPRS) Bhakti Sumekar Sumenep with mark original sample of 0.442.4) style leadership influential significant to performance mediated work by productivity Work employees of the Sharia People's Financing Bank (BPRS) Bhakti Sumekar Sumenep with mark original sample of 0.240.